Hubungan Derajat Skor CARS dengan Tingkat IQ pada Anak dengan Gangguan Autistik di Pusat Terapi Perilaku AGCA Center Surabaya - , ANDI CHRISTIANTO; , Prof. Dr. dr. Edith Humries Pleyte, SpKJ (K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : In the last ten years, there are more children at age 2..5years, and even 8-12 years get autistic signs, especially malfunction of communication, disability of social interaction and maladaptivebehavior. The reported cases (prevalence) of autistic children in Indonesia increases from time to time. At some general hospitals in big cities, more patients with mild to severe developmentaldisorders are refered. To evaluating autistic disorders, a practical and objective instrumentis needed. Today, the most utilized instrument is CARS (Childhood Autism Rating Scale), There are two terms used for autistic children, High Functioning Autism and Low FunctioningAutism. Generally, these two terms are related to the IQ test result. Thus, each autistic child with High Functioning Autism or Low Functioning Autism can obtain an exact behaviouraltherapy.